Dining During the New Normal: A Pilot Study Identifying Factors Influencing the Restaurant Choices of Young Adults in Indonesia - Onna Anieqo Tanadda; Prabu Wardono (Pusat Publikasi Ilmiah, 2023)
The COVID-19 pandemic has brought significant changes to the restaurant industry, including changes in consumer behavior and preferences. In Indonesia, young adults are a significant market segment for restaurants, and understanding their restaurant choices is crucial for the industry's survival. Despite the discussions about the massive impact of the COVID-19 pandemic on the hospitality industry by practitioners and researchers, only a limited number of papers have empirically examined consumer behavior in the context of restaurant choice in Indonesia. Consumers' concerns about safety and social distancing may lead to the permanent closure of some restaurants due to the absence of visitors. As restaurants develop comprehensive reopening plans, consumers may still have specific considerations when choosing a restaurant. This pilot study aims to evaluating acceptability of methods and instruments to participants in identifying consumers' behavior factors that driven their restaurant choice to dine-in during the New Normal period. The sample was composed of 50 young adult consumers from different cities in Indonesia with a moderate risk increase of COVID-19 cases. An adapted 76 item questionnaire with 5-point scales was administered online using Microsoft form and analyzed in SPSS 26 software. After excluding 14 item, the result showed that the number of 62 item were valid and reliable for data analysis. Therefore, the results of this pilot study have implications for subsequent quantitative research, with one of the methods being statistical analysis, specifically factor analysis.